An Application of Radio Acoustic Sounding System (RASS) with Equatorial Atmosphere Radar (EAR) for Continuous Measurement of Atmospheric Virtual Temperature over Kototabang, West Sumatera - Eddy Hermawan (Institut Teknologi Bandung, 2003)
We have introduced a new Equatorial Atmosphere Radar (EAR) in a collaboration project between Radio Science Center for Space and Atmosphere (RASC), Kyoto University, Japan and the Indonesian National Institute of Aeronautics and Space (LAPAN) at Kototabang, Bukittinggi, West Sumatera. This radar is mainly designed to observe winds and turbulence in the troposphere and lower stratosphere with a good time and spatial height resolution. Numerous studies or research programs with the EAR have been planned. One of them is the observation of fine structure in the vertical profile of atmospheric temperature using Radio Acoustic Sounding System (RASS). Since the full instruments are under construction, we present in this paper a brief review of the basic principle of RASS, especially on the design of an acoustic transmitter measurements with EAR. Aan example the comparison between RASS and radiosonde data on 6 November 2001 is also presented.